2012
DOI: 10.1111/j.1477-9552.2012.00346.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mandatory Agro‐Environmental Policy on Farm Fertiliser and Pesticide Expenditure

Abstract: EU farmers are subject to mandatory cross-compliance measures, requiring them to meet environmental conditions to be eligible for public support. These obligations reinforce incentives for farmers to change their behaviour towards the environment. We apply quasi-experimental methods to measure the causal relationship between cross-compliance and some specific farm environmental performance. We find that cross-compliance reduced farm fertiliser and pesticide expenditure. This result also holds for farmers who p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 20 publications
1
20
0
1
Order By: Relevance
“…The outcome variables include fertilizer expenditure per mu (1mu = 1/15 hectare) and pesticide expenditure per mu. Consistent with Jaraite and Kažukauskas (), expenditures are used rather than quantities because of significant diverse units of fertilizer and pesticide measurements used among farmers. The fertilizers used by farmers include farmyard manure, organic fertilizers and/or chemical fertilizers, and the pesticides contain chemical and/or biological pesticides.…”
Section: Data Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The outcome variables include fertilizer expenditure per mu (1mu = 1/15 hectare) and pesticide expenditure per mu. Consistent with Jaraite and Kažukauskas (), expenditures are used rather than quantities because of significant diverse units of fertilizer and pesticide measurements used among farmers. The fertilizers used by farmers include farmyard manure, organic fertilizers and/or chemical fertilizers, and the pesticides contain chemical and/or biological pesticides.…”
Section: Data Descriptionmentioning
confidence: 99%
“…The fertilizers used by farmers include farmyard manure, organic fertilizers and/or chemical fertilizers, and the pesticides contain chemical and/or biological pesticides. The independent variables are selected based on the existing literature on off‐farm work participation and farm input use (e.g., Abdulai & Delgado, ; Chang & Mishra, ; Jaraite & Kažukauskas, ; Matshe & Young, ; Owusu et al., ; Phimister & Roberts, ).…”
Section: Data Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agri‐environmental payments may, in some cases, be necessary to motivate farmers to adopt environmentally friendly technologies. As Jarait≐ and Kažukauskas () conclude, cross‐compliance can be considered as a first step in improving the environmental performance of farms because ‘cross‐compliance reduced farm fertiliser and pesticide expenditure’.…”
Section: Introductionmentioning
confidence: 99%
“…Sneeringer () has used a DID approach to examine the effects of environmental regulations on the structure of the Californian dairy industry, finding evidence that regulation has led to a decline in the size of the industry in Southern California where there are more restrictive regulations. Jarait≐ and Kažukauskas () used a cross‐country DID analysis and concluded that cross‐compliance rules lead to a significant reduction in farm expenditure on fertiliser and pesticide. Sauer et al .…”
Section: The Policy Evaluation Problem and Difference‐in‐difference Amentioning
confidence: 99%